A study on customer satisfaction in using the TMTOUCH services provided by Telekom Cellular Sdn. Bhd. around Malacca area / Noor Affendy ldris - ldris, Noor Affendy (Faculty of Business and Management, 2001)
Satisfying customers are one of the factors that are being given priority by many service organizations. This project paper mainly, focusing on the level of customer's satisfaction towards network and counter services provided by TMTOUCH Malacca. The objective of this research is to identify whether customers are satisfied with the service network and counter services provided and to look for their main problem in using the service TMTOUCH management is aware that customer service comes first as TMTOUCH, mission is to provide total customer satisfaction with excellent services and superior products through smart partnership delivered by professionals of high Integrity in a dynamic and caring organization".